(untitled) (International conference on multidisciplinary science, 2024)
This study focuses on "Behavior management" and emphasizes the importance of monitoring and managing emotional intelligence in individuals within the field of psychology. The psychological, social, and practical aspects of emotional leadership are analyzed in the research. The results indicate that emotional leadership plays a significant role in reducing stress, improving health, and achieving goals for individuals. The study explores strategies for managing emotional intelligence, such as empathy and self-motivation, as well as the influence of the social environment. Practical recommendations are provided at the end of the study, opening up new directions for future research.